Profiling Serum Cytokines and Anticytokine Antibodies in Psoriasis Patients - Dan Hong; Xiuting Liu; Xiaonan Qiu; Siyao Lu; Yanyun Jiang; Guozhen Tan; Zhenrui Shi; Liangchun Wang (Journal of Immunology Research)
Cytokines like IL-17A have been consistently found to be elevated in psoriatic lesional skin, and therapeutic antibodies to IL-17 have demonstrated efficacy in treating psoriatic skin and joint disease. However, results about the circulating cytokines in psoriasis patients remained controversial. Anticytokine autoantibodies (ACAAs) were detected in various autoimmune diseases but remained largely unknown in psoriasis. We aimed to investigate the serum levels of cytokines and ACAAs in psoriasis patients. The study included 44 biologics-naive psoriasis patients and 40 healthy controls. Serum cytokines and the corresponding autoantibodies were measured by multiplex bead-based technology. The bioactivity of serum IL-17A was determined by IL-8 production in primary keratinocytes. Herein, we found serum levels of IL-12B (median: 6.16 vs. 9.03, p=0.0194) and Th17 cytokines (IL-17A: median: 0.32 vs. 1.05, p=0.0026; IL-22: median: 4.41 vs. 4.41, p=0.0120) were increased in psoriasis patients. More interestingly, bioactive IL-17A was identified in a proportion of patients and positively correlated with disease severity. A few of cytokines were closely associated with each other and formed into a distinct panel in psoriasis. Of 13 anticytokine antibodies, anti-IL-22 was moderately lower (median: 262.8 vs.190.5, p=0.0418), and anti-IL-15 was slightly higher (median: 25.5 vs. 30.5, p=0.0069) in psoriasis than controls. None of ACAAs was related to disease severity. Consequently, the ratios of antibodies to cytokines varied with the pattern of cytokines. In summary, our finding suggested that the levels of circulating bioactive IL-17A were associated with disease activity in psoriasis patients. In contrast, the titers of ACAAs were not significantly altered nor correlated with disease severity. However, the functionality of ACAAs remains to be further demonstrated in vitro in future studies.